2007
DOI: 10.1095/biolreprod.106.059113
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles Linked to the Hormonal Induction of Male-Effect Pheromone Synthesis in Goats (Capra hircus)1

Abstract: The male effect is a well-known phenomenon in female sheep and goats whereby a pheromone-induced activation of reproductive function occurs. However, the molecule(s) involved in this phenomenon are unknown. We investigated gene expression profiles for the induction of male effect pheromone synthesis using a PCR-based cDNA subtraction strategy. We constructed two subtracted cDNA libraries using mRNA from the skin of the head or rump region of orchidectomized male goats with or without pheromone induction using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Here, the expression of 5 genes known to function in steroid synthesis or metabolism were significantly differentially expressed in CRPC versus RAD. They are 24-dehydrocholesterol reductase ( DHCR24 ) [113], dehydrogenase/reductase SDR-family member 7 ( DHRS7 ) [114], elongation of long chain fatty acids family member 5 ( ELOVL5 ) [115,116], hydroxysteroid (17-beta) dehydrogenase 4 ( HSD17B4 ) [117], and opioid receptor kappa 1 ( OPRK1 ) [118]. Increased levels of expression of these genes may be indicative of the influence of adrenal androgens, or the local synthesis of androgen, to reactivate the AR to promote the progression of prostate cancer in the absence of testicular androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the expression of 5 genes known to function in steroid synthesis or metabolism were significantly differentially expressed in CRPC versus RAD. They are 24-dehydrocholesterol reductase ( DHCR24 ) [113], dehydrogenase/reductase SDR-family member 7 ( DHRS7 ) [114], elongation of long chain fatty acids family member 5 ( ELOVL5 ) [115,116], hydroxysteroid (17-beta) dehydrogenase 4 ( HSD17B4 ) [117], and opioid receptor kappa 1 ( OPRK1 ) [118]. Increased levels of expression of these genes may be indicative of the influence of adrenal androgens, or the local synthesis of androgen, to reactivate the AR to promote the progression of prostate cancer in the absence of testicular androgens.…”
Section: Discussionmentioning
confidence: 99%
“…In the pheromone synthesis cascade, dihydrotestosterone, after being converted from testosterone by 5α‐reductase, is shown to play a prerequisite role (35, 36). Our cDNA subtraction study has revealed that genes for two enzymes, stearoyl‐CoA desaturase 1 (SCD1) and elongation of the long chain fatty acid family member 5 (ELOVL5), show more than 100‐fold higher expression levels in pheromone‐positive skin samples compared to the control (37). An in situ hybridisation study has confirmed that mRNAs for SCD1 and ELOVL5 are expressed in the sebaceous gland of the head skin of mature male, but not castrated, goats (38).…”
Section: Production Of Pheromonementioning
confidence: 99%
“…Interestingly, 'male effect' pheromone activity is also induced in female skin by androgens [9]. We found that expression of the genes for elongation of long-chain fatty acids family member 5 (ELOVL5) and stearoyl-CoA desaturase 1 (SCD1) increased significantly, concomitant with induction of pheromone synthesis, in three types of skin models, i.e., the head skin of Ttreated orchidectomized (ODX) male goats, rump skin of DHT-treated ODX male goats and head skin of DHT-treated ovariectomized female goats, thereby implicating these two genes as prime can-didates for pheromone synthesis [10].…”
mentioning
confidence: 99%